Índices avaliativos de qualidade na cadeia primária da suinocultura na região norte - RS - Lamb, Roseli Maria (2013)
The Government, health authorities, and especially consumers, require that farms develop and apply quality management concepts in their production processes, and with increasing globalization quality management processes in pigs has been recognized internationally, ensuring the production within the demands of good farming practice. And Globalgap is an example of this reference that can be adopted. The aim of this study was to propose a Checklist adapted from the indicators of Globalgap, which allows to diagnose pig production systems in relation to the environment and the management of good manufacturing practices. The methodology for data collection took place in pig properties located in the northern region of Rio Grande do Sul, the statistical data were evaluated with descriptive analysis determining the cumulative frequency of each issue, and the data that was raised had a classification system following the five-point Likert scale with verbal anchors, serving as a basis for implementation of the research field. Working properties was evaluated by the integrated system, belonging to two cooperatives, being determined to sample in 30 farms. The issues that were parsed from the checklist had procedures for classification on the scale, where the score under frequency has reached a minimum of 54.76% and maximum of 66.32%, that of the total evaluated, with these data it can concluded that the farms evaluated are classified in the "average" score, because the pig owners holds the knowledge in practice, but it is evident that part of documentary records management is failed and this is an opportunity for improvement that should be deployed to ensure evaluative indices. But for that the region is able to export products to the EU, or to go through the process of certification of management be it environmental or quality, it will be necessary to implement some procedures that improve practices in the use of natural resources. And yet the validation checklist is by applying the method of cronbach's alpha, which determined how reliability index of 0.614 research, soon with the data surveyed may conclude that the region through the processes of cooperatives is working for you in the near future fingertips indexes to ensure that the conditions for certification of production processes.